The Mata Azul pegmatitic field, Tocantins/Goiás, central Brazil: geology, genesis and mineralization - Queiroz,Hudson de Almeida (2018)
ABSTRACT: In Goiás and Tocantins States, Central Brazil, several granitic pegmatites were characterized and grouped for the first time. These pegmatites had been intensely explored by hand in the past, producing mainly gemstone varieties of tourmaline and beryl. Barren, beryl- and tourmaline-bearing pegmatites occur across an area of 2,000 km 2 where they intrude regional metasedimentary rocks and peraluminous granites. K-feldspar (mostly altered to kaolin), quartz and mica (mainly muscovite) are the major minerals. The main accessory minerals are beryl, tourmaline, garnet, albite, Fe-Mn phosphate aggregates, and trilithionite. The paragneiss surrounding the barren pegmatites was affected by thermal metamorphism and later hydrothermal alteration, producing Ca-silicates, Ti-Nb-Y oxides and sulfides. Leucogranites of the Mata Azul Suite are peraluminous and syn- to post-orogenic with geochemical characteristics of the LCT granite-pegmatite group. LA-ICP-MS U-Pb geochronology in monazite yields an age of 519 ± 2.8 Ma. Additionally, U-Th-Pb chemical dating of uraninite reveals a maximum age between 500 and 560 Ma. These ages, the field relationships, the mineralogy and the geochemical data suggest that the granites of the Mata Azul Suite are the probable sources of the studied pegmatites. The mineral associations and the mineral chemistry are used to define the degree of fractionation of the pegmatites. We propose that the group of studied pegmatites represents a pegmatitic field, called the Mata Azul Suite Pegmatitic Field.